2017
DOI: 10.3233/isu-170853
|View full text |Cite
|
Sign up to set email alerts
|

Advancing library cyberinfrastructure for big data sharing and reuse

Abstract: Abstract. Data-intensive science presents new opportunities as well as challenges to research libraries. The cyberinfrastructural challenge, although chiefly technological, also involves social-economic and human factors, therefore requires a deep understanding of what roles research libraries should play in the research lifecycle. This paper discusses the rationale and motivations behind a research project to investigate effective library big data cyberinfrastructure strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…95 Xie and Fox explored the roles that research libraries should play in the research lifecycle and discuss the motivations behind a research project to investigate effective library Big Data cyberinfrastructure strategies. 96 These papers present several possibilities and opportunities for the use of Big Data in research libraries, focusing on the analysis, management, and preservation of research data. Literature review indicated that understanding how researchers interact with their data at various points in the lifecycle can help librarians develop targeted services to meet the particular needs of researchers at their institutions and also enhance their services by implementing big data technologies.…”
Section: Big Data In Research Librariesmentioning
confidence: 99%
“…95 Xie and Fox explored the roles that research libraries should play in the research lifecycle and discuss the motivations behind a research project to investigate effective library Big Data cyberinfrastructure strategies. 96 These papers present several possibilities and opportunities for the use of Big Data in research libraries, focusing on the analysis, management, and preservation of research data. Literature review indicated that understanding how researchers interact with their data at various points in the lifecycle can help librarians develop targeted services to meet the particular needs of researchers at their institutions and also enhance their services by implementing big data technologies.…”
Section: Big Data In Research Librariesmentioning
confidence: 99%
“…In other words, even if we can afford to build a query system that can hold all 40 petabytes of data, it is still more efficient to use this system only to partition the larger data set instead of directly handling batch analytics. Therefore, the suitable cyberinfrastructure pattern to reuse web archives should always be the "Bridge" [57], where archival files are stored separately from where the data are to be processed.…”
Section: Reuse Web Archives As Big Data Sourcesmentioning
confidence: 99%
“…For web archiving applications, Warcbase [33] chooses to load WARC files into HBase for querying. As such, archived data will need to persistently occupy the analytical systems, as in the "Network" pattern [57]. This is not suitable for long-term preservation.…”
Section: Related Workmentioning
confidence: 99%
“…The role of librarians is essential for Big Data analytics, so there is a need to improve the skills and knowledge of librarians for the implementations of Big Data analytics. Xie and Fox (2017) argued that for the application of Big Data analytics, the library professionals do not have as such expertise to provide new value-added services. In this context, the research of Atkinson (2018) reveals that there is a need of client-centric approach for LIS professionals to be more integrated into the academic process and to understand and support different phases of research-based needs of library users.…”
Section: Big Data Analytics In Librariesmentioning
confidence: 99%